Tinjauan Implementasi Penyetaraan Jabatan Administrasi ke Jabatan Fungsional di Sekretariat Daerah Provinsi Riau: Analisis Kebijakan Organisasi - Saputri, Adriana; Ummul Fithriyyah, Mustiqowati (Universitas Serang Raya, 2024)
This study aims to determine the implementation of the regulation of the Minister of Administrative Reform and Bureaucratic Reform number 17 of 2021 concerning the equalization of administrative positions into functional positions at the Organization Bureau of the Regional Secretariat of Riau province. The type of research used in this journal is a type of qualitative research. The method of data collection that the authors use in this study is the technique of observation, interviews, and documentation with informants in the organizational Bureau of the Regional Secretariat of Riau province. Based on the results of research related to the implementation of the regulation of the Minister of Administrative Reform and Bureaucratic Reform number 17 of 2021 on the equalization of administrative positions into functional positions at the Riau provincial secretariat Organization Bureau, the results obtained that the equalization of administrative positions into functional positions at the riau provincial secretariat Organization Bureau has been implemented properly and on time. In its implementation, there are constraints in proposing the name of the functional position that matches the previous structural position to fill the functional position to be equalized. In addition, many functional officials who still do not understand the job system and mechanism of work as a functional position.